Penerapan Metode Graphic Organizer untuk Meningkatkan Kemampuan Menulis Teks Opini Mahasiswa Program Studi Manajemen di Undiknas Denpasar - devi kalfika (Jurnal Ilmiah Manajemen & Bisnis, 2017)
This research was conducted based on the obstacles experienced by the students of management department of Undiknas Denpasar to write opinions text. The problem lies in the difficulty of organizing ideas, developing the principal ideas, the accuracy of selection diction, and the use of spelling. In relation to the problem, a proper teaching method is needed to handle it. Given the ability to write popular scientific papers is very important mastered to support the ability of students in writing more complex scientific papers. The method used in this Classroom Action Research  is Graphic Organizer Method. The results of this study indicate a significant increase in the ability of students in writing opinions text. This is evidenced by the increase in the average student score in each cycle. The average value of students in the first cycle was 65, this score then increase again in the second cycle to 72, and in the third cycle, the students could reach 78 average score. Keywords: writing, opinion text, graphic organizer method, PTK